Սուրբ Գրիգոր Նարեկացու «Մատեան ողբերգութեան» երկը քրիստոնէական մատենագրութեան համապատկերում - Ղազարեան, Նորայր (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Поэма «Книга скорбных песнопений» рассматривается в контексте христианской литературы, что помогает воссозданию общих литературноисторических закономерностей. Поэма — это жанр молитвы, а молитва рассматривается как возможность для беседы с Богом. Псалмы — это молитвы, лежащие в основе как содержания, так и структуры поэмы «Книга скорбных песнопений». Связь поэмы с неоплатонизмом рассматривается как реальность, опосредованная святоотеческой литературой. Отношения между мистицизмом и теологией были четко представлены. Поэма Нарекаци впервые рассматривалась как онтологическая поэма, чем и обусловлена его художественная гениальность.Заслуживают внимания откровения о специфической связи с поэтическими книгами Ветхого Завета. “The Book of Lamentations”, poem by Gregory of Narek is considered in the context of Christian literature, which helps to bring out general literary and historical patterns. The poem is written in a genre of prayer, and prayer is seen as an opportunity for conversation with God. The psalms are the prayers that underlie both the content and structure of “The Book of Lamentations”. The connection of the poem with Neo-Platonism is seen as a reality mediated by patristic literature. The relationship between mysticism and theology has been clearly elucidated. First, the poem of Gregory of Narek was seen as an ontological poem, which accounts for his artistic genius. Noteworthy are the disclosures of a specific connection to the poetic books of the Old Testament.
Keywords: Հաղորդումներ